Multicultural Crew Communication Challenges and SMCP Utilization in Mixed-Nationality Shipboard Environments: A Qualitative Study Among STIP Jakarta Graduates - Suhartini Suhartini; Renta Novaliana Siahaan; Marudut Bernadtua Simanjuntak (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
The Standard Marine Communication Phrases are designed to provide a shared communicative framework for multinational seafaring crews, yet the adequacy of SMCP training in preparing graduates for the actual linguistic and cultural complexity of mixed-nationality shipboard communication environments remains empirically underexamined from the perspective of those who have experienced both the institutional training and the real-world professional context it is intended to prepare them for. This study investigates multicultural crew communication challenges and SMCP utilization patterns through a qualitative inquiry involving STIP Jakarta graduates currently serving in mixed-nationality shipboard environments, SMCP lecturers, and shipping company safety and communication managers. Data were collected between April 2025 and April 2026 from twenty-seven participants across these three groups through focus group discussions and semi-structured interviews. Thematic analysis, cross-group comparison, and narrative synthesis were applied. Findings reveal that STIP Jakarta graduates experience four categories of post-training communicative challenge in mixed-nationality environments: SMCP deviation toward informal English, authority-gradient communication suppression, native speaker assumption disadvantage, and SMCP phrase non-recognition among non-training recipients such as non-STCW crew categories. Graduates' retrospective assessment of STIP Jakarta's SMCP training as adequate for exam performance but insufficient for multicultural communicative reality constitutes the study's central cross-group finding and provides the most direct evidence for curriculum reform. The study contributes a graduate-grounded, post-training account of SMCP multicultural communication challenge that institutional-level curriculum assessment cannot supply.